2013
DOI: 10.1371/journal.pone.0075651
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium jeikeium jk0268 Constitutes for the 40 Amino Acid Long PorACj, Which Forms a Homooligomeric and Anion-Selective Cell Wall Channel

Abstract: Corynebacterium jeikeium, a resident of human skin, is often associated with multidrug resistant nosocomial infections in immunodepressed patients. C. jeikeium K411 belongs to mycolic acid-containing actinomycetes, the mycolata and contains a channel-forming protein as judged from reconstitution experiments with artificial lipid bilayer experiments. The channel-forming protein was present in detergent treated cell walls and in extracts of whole cells using organic solvents. A gene coding for a 40 amino acid lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 73 publications
(92 reference statements)
1
29
0
Order By: Relevance
“…5) having one side highly hydrophobic and another side hydrophilic and charged. This organization is presumably sufficient for the stabilization and anchorage in the mycolic acid layer as has been observed in PorH from C. efficiens, PorA from C. callunae and PorACj from C. jeikeium (Abdali et al, 2013;Hünten et al, 2005a, b).…”
Section: Secondary Structure Predictionsmentioning
confidence: 74%
See 1 more Smart Citation
“…5) having one side highly hydrophobic and another side hydrophilic and charged. This organization is presumably sufficient for the stabilization and anchorage in the mycolic acid layer as has been observed in PorH from C. efficiens, PorA from C. callunae and PorACj from C. jeikeium (Abdali et al, 2013;Hünten et al, 2005a, b).…”
Section: Secondary Structure Predictionsmentioning
confidence: 74%
“…However, there are some microbial pore-forming proteins where a-helix structures are relevant for their stability, such as PorH from Corynebacterium glutamicum, C. efficiens, C. callunae and PorACj from C. jeikeium (Abdali et al, 2013;Hünten et al, 2005a, b). Other proteins, like PorA from M. tuberculosis, have an N-terminal domain with both a-helix and b-sheet secondary structures (Teriete et al, 2010;Yang et al, 2011).…”
Section: Secondary Structure Predictionsmentioning
confidence: 99%
“…However, some exhibit cation selectivity (as in D. maris) whereas others are anion-selective, although it is likely that each organism will possess channels with both types of selectivity in order to facilitate uptake of the full range of hydrophilic solutes. More interestingly, some porins appear to work as hetero-oligomers [18,46] whereas others form likely homo-oligomers [47].…”
Section: Comparison Of the Cell Wall Channel Properties Of D Maris Amentioning
confidence: 99%
“…In the closely related Corynebacterium species C. glutamicum and C. efficiens , porA and porH genes encode for PorA and PorH proteins, which assemble for large, water-filled cell wall pores [ 27 30 ]. We could also previously demonstrate that a channel-forming protein, named PorACj, was identified in the known genome of C. jeikeium by the similar chromosomal localization of its gene to the known porH and porA genes of other Corynebacterium strains [ 31 ]. However, in contrast to certain Corynebacterium species, where two polypeptides PorA and PorH are needed to form a functional cell wall pore, the pore in the cell wall of C. jekeium is formed by a single polypeptide PorACj [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In all other cases, the genes are located in tandem between the genes coding for the chaperone GroEL2 and the polyphosphate kinase PKK2 [ 30 ]. So far, we demonstrated that PorACj is the smallest polypeptide forming well defined and stable channels [ 31 ]. The complete genome sequence of C. urealyticum DSM 7109 is known [ 13 ].…”
Section: Introductionmentioning
confidence: 99%